(3GdQjGVjGJ GdeGdjIs - (3TbjQj fhQj(B, (3ehSis; (3hdjO CMeO UGaj(B, s ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2011)
(3GddhZGQjJe h GdGSS h GdLPhQ, GdeYGOdGJ h GdeJhGdjGJ , GdQHG h HjGf McegG GdTQYj h GdJWQb Gdi CVQGQgG, GdaGFOI h GdaGFOI GdeQcHI , GSJgdGc GdbQhV WhjdI GdCLd HaGFOI eQcHI, Jbjje GdSfOGJs
Keywords: (3GdEbJUGO GdJMdjdjs; (3GdEbJUGO GdQjGVjs